Translating theory into practice: a flexible decision-making tool to support the design and implementation of climate-smart agriculture projects - Walsh, Conor; Renn, Mara; Klauser, Dominik; de Pinto, Alessandro; Haggar, Jeremy; Rouf Abdur; Hopkins, Richard J.; Farhad Zamil (Elsevier, 2024)
Context: Climate-smart agriculture (CSA) is a conceptual framework for responding climate-related risk in agriculture across the three pillars of Mitigation, Resilience, and Production. Existing tools have been developed which seek to operationalize the CSA concept to evaluate and benchmark progress; each of which have their own relative strengths and weaknesses. Objective: The translation of this concept into actionable projects/portfolios hence requires the careful evaluation of potential trade-offs and synergies between these three pillars. The hereby presented decision-making tool aims to offer a basis for a structured evaluation of such trade-offs and synergies. Methods: It does so by assessing five different outcome pathways on how they contribute to a project's performance across the three pillars of CSA. We aspire that the use of this tool will allow for more deliberate design and implementation of projects in agricultural development, increasing the resilience and productivity of farming systems whilst ensuring the sustainable use of the environmental resource-based agriculture depends on. Results and conclusions: This tool was applied in a workshop setting to evaluate the relative strengths and weaknesses of two distinct projects; demonstrating the utility in visualizing the same performance in different ways. Of particular importance was ability to demonstrate how focusing on productivity and adaptation may trade-off mitigation activities. Significance: The results of the case study application demonstrated the challenge in meeting all the CSA requirements; particularly where the main objective of a project is to enhance and increase productivity. This reinforces how supporting all three pillars is challenging for a single project and therefore CSA is arguably more achievable when viewed in terms of a portfolio of activities which can collectively compensate for the limitations of a single project.